Examining social equity in transportation asset management: current status and integration approaches - Khalife, Fawzi Ghazi, author; Atadero, Rebecca, advisor; Ozbek, Mehmet, advisor; Grigg, Neil, committee member; Arneson, Erin, committee member; Malin, Stephanie, committee member (Colorado State University. Libraries, 2025)
Transportation is a critical component of the built environment, vital for ensuring access to essential services and opportunities. In the U.S., transportation systems have expanded significantly since the rise of the automobile and the development of the Interstate Highway System. While these advancements have enhanced connectivity and accessibility, they have also had detrimental effects on many communities. Research shows that low-income and racially minoritized groups are disproportionately impacted by displacement, pollution, and substandard transportation infrastructure. This disparity has raised concerns about social equity among transportation professionals, which commonly refers to the fair distribution of benefits and burdens associated with transportation systems. Transportation asset management (TAM) is one subsector of transportation where social equity remains overlooked. TAM is centered on the operation and maintenance of transportation systems, traditionally prioritizing economic factors while giving minimal attention to social and equity factors in decision-making. To address this issue, this dissertation explores the integration of social equity – referred to as equity in this study – within TAM, identifies strategies for effectively incorporating equity into TAM practices, and analyzes the challenges faced in this process. This research is organized into three studies designed to highlight equity-related issues in TAM and promote the integration of equity into TAM practices. The first study (Chapter 2) investigated the incorporation of equity within TAM by analyzing the 2019 TAM plans from all U.S. states. The findings revealed that equity remains neglected in these plans, with many in the sector failing to integrate equitable practices. This underscored the need for further research on equity in the context of TAM. Additionally, the study reviewed existing guides and sustainability rating systems that can assist in managing assets to promote equity. These resources provide definitions and indicators of equity that TAM professionals can utilize as a foundation, allowing them to adapt and expand upon these frameworks to address the specific needs of their communities and achieve equitable outcomes. The second study (Chapter 3) involved conducting interviews with professionals engaged in integrating equity into transportation to gain deeper insights into the challenges they encounter. Recognizing that transportation sectors outside of asset management have made greater progress in integrating equity into practice, this study included a diverse sample of 29 professionals from local governments, community-based organizations, and departments of transportation. This approach reflects the varied backgrounds and expertise of those engaged in equity work within the transportation sector. Utilizing semi-structured interviews and thematic analysis, the author categorized equity-related challenges into four themes: definitions, metrics and data, community engagement, and organizational challenges. This research enhances the understanding of these challenges and explores strategies for effectively addressing them, facilitating the successful integration of equity across various transportation sectors, including TAM. The third study (Chapter 4) surveyed TAM engineers and professionals to understand whether and how equity is currently incorporated in their practices and decision-making processes. The respondents provided information about their work in TAM and equity, sharing their expert opinion on equity-related issues. The findings indicated that while equity remains neglected within TAM, there are existing efforts and initiatives that could be enhanced to promote equity. Respondents noted that there is not a singular approach to advancing equity in TAM and that several challenges hinder the process, particularly in measuring equity, securing funding for equity programs, and defining equity in the context of TAM. This understanding of equity in TAM can empower TAM professionals to better understand and advance equity in their work. This dissertation offers a deep understanding of equity in the context of transportation and TAM. It concludes by offering insights and resources that enable engineers and professionals in TAM to define and measure equity in their work, implement actionable strategies, and develop plans to advance equity while managing associated challenges. The findings aim to assist TAM professionals in refining their practices to better address community needs and deliver equitable outcomes, ultimately advancing social justice through transportation infrastructure and assets.
Keywords: transportation asset management; social equity; transportation planning